African American Undergraduate Students’ Perceived Welcomeness at a Midsized University Library - Duffin, Kirstin I.; Corrigan, Ellen K. (Evidence Based Library and Information Practice, 2023)
Objective – This project assessed African American students’ feelings of comfort and belonging about engaging with library resources and services at a public regional comprehensive university in the midwestern United States.Methods – This study used an explanatory sequential design. First, we surveyed degree-seeking African American undergraduates on their perceived welcomeness regarding the library’s collections and spaces, staff and users, and atmosphere and marketing. We then recruited focus group participants from the survey, and in focus group sessions, participants expanded on feedback provided in the survey, with particular emphasis on their feelings about their interactions and experiences with the library.Results – Most students who participated indicated the library is a place where they felt safe and welcomed, although the library felt to some like a neutral space rather than a place that actively supported them. Focus group participants shared several easily implementable suggestions for making the library a more attractive campus space for African American students.Conclusion – Student recommendations will shape the services we provide for an increasingly diverse student body. Changes to make the library as physical place more welcoming include exhibiting student artwork and featuring African American themes in displays. The library as a social space can become more welcoming in several ways. Hiring a diverse staff and providing staff training on diversity and equity topics, offering engaging student opportunities for congregation in the library, and collaborating with African American student organizations will help to foster a sense of belonging among these students. Facilitating opportunities for connection will contribute to African American undergraduates’ academic success.